Reducing gender bias in the evaluation and selection of future leaders: The role of decision-makers’ mindsets about the universality of leadership potential. - Liu, Zhi; Rattan, Aneeta; Savani, Krishna (Journal of Applied Psychology, 2023)
). Five studies investigated the relationship between these mindsets and decision-makers' gender biases in leader evaluation and selection decisions. The more senior government officials in China held a universal mindset, the less they showed gender bias when rating their subordinates' leadership capability (Study 1). Working adults in the United Kingdom who held a more universal mindset exhibited less gender bias when evaluating and selecting job candidates for a leadership position (Study 2). In an experiment, Singaporean students exposed to a universal mindset exhibited less gender bias when evaluating and selecting candidates than those exposed to a nonuniversal mindset (Study 3). Another experiment with working adults in China replicated this pattern and added a control condition to confirm the directionality of the effect (Study 4). Last, Study 5 showed that a more universal mindset was associated with less gender bias particularly among decision-makers with stronger gender stereotypes in the domain of leadership. This research demonstrates that, although they are seemingly unrelated to gender, mindsets about the universality of leadership potential can influence the extent to which people express gender bias in the leadership context. (PsycInfo Database Record (c) 2023 APA, all rights reserved).